Prognostic significance of myocardial salvage assessed by cardiac magnetic resonance in reperfused ST-segment elevation myocardial infarction - Li, Yunling; Wang, Guokun; Wang, Xueying; Li, Ye; Zhao, Yanming; Gu, Xia; Xu, Bing; Cui, Jinjin; Wang, Xuedong; Sun, Yong; Liu, Shengliang; Yu, Bo (Frontiers in Cardiovascular Medicine, 2022)
Aims: Myocardial salvage index (MSI) is attracting increasing attention for predicting prognosis in acute myocardial infarction; however, the evaluation of MSI is mainly based on contrast agent-dependent cardiac magnetic resonance (CMR) scanning sequences. This study aims to investigate the prognostic value of MSI in reperfused ST-segment elevation myocardial infarction (STEMI) through contrast agent-free CMR technique. Methods and results: Nighty-two patients with acute STEMI underwent CMR after primary percutaneous coronary intervention were enrolled. Patients were subcategorized into two groups according to median MSI. T1 and T2 mapping were conducted for measuring infarct size (IS) and area at risk (AAR). IS was significantly larger in < median MSI group than ≥ median MSI group (P < 0.001). AAR between two groups showed no obvious differences (P = 0.108). Left ventricular ejection fraction (LVEF) was obviously lower in < median MSI group than ≥ median MSI group (P = 0.014). There was an obvious inverse correlation between MSI and reperfusion time (R = -0.440, P < 0.001), and a strong inverse correlation between MSI and IS (R = -0.716, P = 0.011). Over a median follow-up period of 263 (227 – 238) days, prevalence of MACEs was significantly higher in < median MSI group (HR: 0.15 [0.04 – 0.62]; Logrank P = 0.008). Univariate Cox regression analysis revealed that LVEF, IS, and MSI were significant predictors for major adverse cardiovascular events (MACEs) (all P < 0.05). In stepwise multivariate Cox regression analysis, LVEF and MSI were identified as independent parameters for predicting MACEs (both P < 0.05). In receiver-operating characteristic analysis, LVEF, IS, MSI showed prognostic value in predicting MACEs with AUCs of 0.809, 0.779 and 0.896 separately (all P < 0.05). Combination of MSI with LVEF showed the strongest prognostic value of MACEs (AUC:0.901, sensitivity: 77.78%, specificity: 98.80%, P < 0.001). Delong’s test showed that combination of LVEF with MSI had incremental value than LVEF itself in predicting MACEs (P = 0.026). Conclusion: Contrast agent-free CMR technique provides reliable evaluation of MSI, which contributes to assess efficacy of reperfusion therapy and predict occurrence of MACEs.